Penggunaan Media Pembelajaran Berbasis Digital dalam Meningkatkan Hasil Belajar - Anisah Fitri; Ari Saptono; Aditya Pratama (CV. Ulil Albab Corp, 2024)
This research was conducted with the aim of determining the direct and indirect influence of internet learning media variables as independent variables and learning activities as intervening variables on student learning outcomes as dependent variables. The method used is a quantitative method. The population of this study consisted of class X students at SMAN 4 Depok in Economics subjects with a sample size of 204 students. The data used in this research are primary and secondary data. Primary data was obtained from distributing questionnaires with 5 alternative answers which were measured using a Likert scale with 11 statements and distributed using Google Forms and secondary data in the form of grades obtained in economics subjects. The data analysis technique uses path analysis using SPSS version 25 software. The research results show that: (1) Internet learning media has a direct effect on student learning outcomes, (2) learning activities have a direct effect on student learning outcomes (3) Internet learning media has a direct effect on learning activities (4) Internet learning media through learning activities has an indirect effect on student learning outcomes.